2015
DOI: 10.3390/polym7061020
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar Fracture Toughness of CFRP Laminates Incorporating Multi-Walled Carbon Nanotubes

Abstract: Carbon fiber reinforced polymer (CFRP) laminates exhibit limited fracture toughness due to characteristic interlaminar fiber-matrix cracking and delamination. In this article, we demonstrate that the fracture toughness of CFRP laminates can be improved by the addition of multi-walled carbon nanotubes (MWCNTs). Experimental investigations and numerical modeling were performed to determine the effects of using MWCNTs in CFRP laminates. The CFRP specimens were produced using an epoxy nanocomposite matrix reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…PC incorporating 1.5% MWCNTs showed the highest increase in fracture toughness. At 1.0 wt.% MWCNTs, fracture toughness increased by 24% showing similar results to that of Yu et al [3], Tang et al [7] and Borowski et al [15] observed due to incorporating MWCNTs in fibre reinforced polymer composites. PCNC-1.5 and PCNC-0.5 showed excessive CMOD to failure and a yieldlike behavior in the curve softening region.…”
Section: Fracture Test Resultssupporting
confidence: 87%
“…PC incorporating 1.5% MWCNTs showed the highest increase in fracture toughness. At 1.0 wt.% MWCNTs, fracture toughness increased by 24% showing similar results to that of Yu et al [3], Tang et al [7] and Borowski et al [15] observed due to incorporating MWCNTs in fibre reinforced polymer composites. PCNC-1.5 and PCNC-0.5 showed excessive CMOD to failure and a yieldlike behavior in the curve softening region.…”
Section: Fracture Test Resultssupporting
confidence: 87%
“…12. Similar C=O peaks were reported before in using COOH functionalized MWCNTs for improving fracture toughness of carbon fiber composites (Borowski et al 2015). It is important to note that that amide peak in the COOH-MWCNTs-epoxy nanocomposite at 1660 cm -1 appears combined with the aromatic and N-H deformation peaks in neat epoxy (Tsai et al 2015).…”
Section: Microstructural Features Of Pcsupporting
confidence: 83%
“…This is because of the non-planar interply structure of woven-fabric composites, the interaction between the delamination crack, the matrix regions and the weave structure during propagation, will result in crack growth [11]. The interlaminar performance are characterized by their weakness towards the sheer stress and tensile stress [12]. According to Zulkifli R et al [1], when the number of layers increases, the stiffness and interlaminar fracture toughness also found to be increasing.…”
Section: Interlaminar Fracture Toughnessmentioning
confidence: 99%